Comparison of corrosion behavior of X52 steel in liquid and supercritical CO2 transport environments with multiple impurities - Yulong Zhao; Tiancong Ding; Shuai Yang; Jiawei Li; Xiaofeng Zhao; Xueqiang Lin; Chong Sun; Jianbo Sun (Corrosion Communications, 2025)
In this study, the corrosion behavior of X52 steel in liquid and supercritical CO2 environments with different water contents and coexistence of O2, SO2, NO2 and H2S gas impurities was investigated by means of mass loss method, surface analysis techniques and water chemistry simulations. The results show that benefiting from more corrosive substances and more corrosive aqueous phase, the corrosion degree of X52 steel in a liquid CO2 environment is larger than that in a supercritical CO2 environment. The formation of corrosion products is not affected by the changed CO2 phase state environment but is greatly affected by the water content in CO2 fluid. The impurities, the product of impurity reactions and the further oxidation of corrosion products jointly dominate the formation of corrosion products on the steel.